EXAMINING BOARD CHARACTERISTICS AND INTEGRATED REPORTING QUALITY: INSIGHT FROM ESG-FOCUSED FIRMS IN INDONESIA - Butar-butar, Dea Tiara Monalisa; Pangestu, Krisnawati Yeni; Itan, Iskandar (Journal of Applied Finance and Accounting, 2024)
This research aims to look at Indonesian firms and see whether there's a connection between board traits and the quality of their integrated reporting. This study analyzes 52 listed firms from the environmental, social, and governance (ESG) index between 2019 and 2022 using linear regression with panel data to test its assumptions. The data was acquired from annual reports of Indonesian corporations. The acquired empirical data clearly shows that gender diversity appears to significantly improve the integrated reporting quality. Also noteworthy is that board size, independence, and CEO duality are not significantly related. This study has several practical implications in addition to its theoretical implications. Managers, shareholders, and policymakers should take note of these findings, as they are particularly relevant. Therefore, stakeholders should evaluate the precision of disclosure when deciding on the best reporting approach. A more accurate assessment of risk, less stock volatility, more long-term value for shareholders, and an improved company reputation are all outcomes of this. Corporate social responsibility and sustainability literature is lacking, which this article seeks to remedy. It fills a gap in the literature by providing more information about ESG company-specific integrated reporting and corporate governance. This study has important implications for professionals and practitioners who want to raise the bar on the quality of their integrated reports.